Influence of the Audit Committee, Independence of the Audit Committee, Audit Tenure and Profitability on Audit Report Lag - Afifah Megarani; Ambar Woro Hastuti; Adi Suprayitno (University of Merdeka Malang, 2022)
The research formulation is how the audit committee, audit committee independence, audit tenure and profitability affect audit report lag in companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. This study aims to analyze the effect of the audit committee, audit committee independence, audit tenure and profitability on audit report lag in companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The research population includes companies that experience delays in financial reporting in 2020, according to the announcement released by the IDX. Sampling using purposive sampling method, and obtained 15 companies as research samples. The data analysis method used is logistic regression analysis. Audit report lag is the time span required to complete the audit of the company's annual financial statements. Many factors can affect the occurrence of audit report lag in a company. The results of the study prove that audit tenure has an effect on audit report lag. Meanwhile, the audit committee, the independence of the audit committee, and partial profitability have no effect on audit report lag. All independent research variables simultaneously affect the audit report lag. The audit committee, audit committee independence, audit tenure, and profitability have an influence on the audit report lag of 37.8%, while 62.2% is influenced by other factors outside the research variables.